Does experience shape subjective expectations? - Tobias Rossmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
This paper documents that individuals' expectations about macroeconomic outcomes are systematically linked with the experiences of these macroeconomic outcomes they have made during life. Focusing on expectations about national inflation, national unemployment and national business conditions, I measure individual-specific experiences as weighted averages of these variables over the respondents' lifetime, respectively. I find that experience significantly predicts respondents' expectations in each of these domains and show that individuals generally put more weight on recent rather than distant years when aggregating past information. The empirical model also allows for heterogeneity with respect to observed socio-economic characteristics. The estimates suggest the existence of a gender effect. Compared to females, males put relatively more weight on distant years when aggregating past information, and the association between expectations and past experiences is generally weaker for men.
Keywords: D84; E24; E31; 330; Expectations; Experience; Inflation; Unemployment; Business conditions